Anxiety sensitivity and mindful attention in terms of anxiety and depressive symptoms and disorders among Latinos in primary care. Issue 1 (30th September 2015) - Zvolensky, Michael J.; Bakhshaie, Jafar; Garza, Monica; Paulus, Daniel J.; Valdivieso, Jeanette; Lam, Hantin; Bogiaizian, Daniel; Robles, Zuzuky; Schmidt, Norman B.; Vujanovic, Anka
Abstract: The present investigation examined the interactive effects of anxiety sensitivity and mindful attention in relation to anxiety and depressive symptoms and psychopathology among 145 adult Latinos (85.5% female; M age =39.9, SD =10.8 and 98.6% used Spanish as their first language) who attended a community-based primary healthcare clinic. As expected, the interaction between anxiety sensitivity and mindful attention was significantly related to number of mood and anxiety disorders, social anxiety, and depressive symptoms. No significant interaction, however, was evident for panic (anxious arousal) symptoms. The form of the significant interaction indicated that Latinos reporting co-occurring higher levels of anxiety sensitivity and lower levels of mindful attention evinced the greatest levels of anxiety/depressive psychopathology, social anxiety, and depressive symptoms. These data provide novel empirical evidence suggesting that there is clinically-relevant interplay between anxiety sensitivity and mindful attention in regard to a relatively wide array of anxiety and depressive variables among Latinos in a primary care medical setting. Highlights: The interactive effects of anxiety sensitivity and mindful attention were examined. Mindful attention was significantly related to depressive symptoms. Anxiety sensitivity was significantly related to anxiety and depressive symptoms.